UTILITY OF REPEATED DRUG LEVEL MEASUREMENTS AFTER HIGH DOSE METHOTREXATE INFUSION FOR TREATMENT PLANNING IN PEDIATRIC LEUKEMIA - Terzi, Özlem; Aycicek, Ali; Uysalol, Ezgi; Yildirgan, Duygu; Sek, Fatma; Bayram, Cengiz (Sanamed, 2022)
Introduction: Although high-dose Methotrexate (MTX) is a successful chemotherapeutic agent used in the treatment of acute lymphoblastic leukemia in childhood, life-threatening toxic effects are rarely seen. Therefore, frequent follow-up of drug levels is recommended. The study researched the necessity of drug level measurement and a minimum safe number of measurements. Materials and Methods: The files of pediatric patients with Acute Lymphoblastic Leukemia receiving high-dose MTX treatment in a single center between 2018 and 2021 were retrospectively reviewed. The treatment protocol was: 3000 mL/m2 alkaline hydration fluid was continued until the 72nd hour together with 2 gr/m2 continuous MTX infusion in the low-risk group and 5 gr/m2 in moderate and high-risk groups, and 15 mg/m2/dose folinic acid was given at the 42nd, 48thand 54th hours. Findings: 456 MTX treatments were evaluated in 114 patients. Similar results (p>0.05) were obtained in the MTX level measurements performed at the 24th, 42nd, 48th, and 54th hours after MTX administration. In the repeated measurements, the data at the 42nd hour were similar (p=0.021). The number of cases that were >150 mmol/L at the 24th hour of methotrexate infusion and above 1 mmol/L at the 42nd, 48th, and 52nd hours were found to be similar in the repeated measurements. Conclusion: Although recommended, frequent follow-up of MTX levels might not always indicate toxicity. In centers with limited laboratory facilities, the MTX level measured at the 42nd hour in the first treatment might be a practical approach to guide the management of other MTX treatments.